Calcium influx in internally dialyzed squid giant axons (The Rockefeller University Press, 1979)
A method has been developed to measure Ca influx in internally dialyzed squid axons. This was achieved by controlling the dialyzed segment of the axon exposed to the external radioactive medium. The capacity of EGTA to buffer all the Ca entering the fiber was explored by changing the free EGTA at constant [Ca++]i. At a free [EGTA]i greater than 200 microM, the measured resting Ca influx and the expected increment in Ca entry during electrical stimulation were independent of the axoplasmic free [EGTA]. To avoid Ca uptake by the mitochondrial system, cyanide, oligomycin, and FCCP were included in the perfusate. Axons dialyzed with a standard medium containing: [ATP] = 2 mM, [Ca++]i = 0.06 microM, [Ca++]o = 10 mM, [Na+]i = 70 mM, and [Na+]o = 465 mM, gave a mean Ca influx of 0.14 +/- 0.012 pmol.cm-2.s-1 (n = 12. Removal of ATP drops the Ca influx to 0.085 +/- 0.007 pmol.cm-2.s-1 (n = 12). Ca influx increased to 0.35 pmol.cm-2,s-1 when Nao was removed. The increment was completely abolished by removing Nai+ and (or) ATP from the dialysis medium. At nominal zero [Ca++]i, no Nai-dependent Ca influx was observed. In the presence of ATP and Nai [Ca++]i activates the Ca influx along a sigmoid curve without saturation up to 1 microM [Ca++]i. Removal of Nai+ always reduced the Ca influx to a value similar to that observed in the absence of [Ca++]i (0.087 +/- 0.008 pmol.cm-2.s-1; n = 11). Under the above standard conditions, 50-60% of the total Ca influx was found to be insensitive to Nai+, Cai++, and ATP, sensitive to membrane potential, and partially inhibited by external Co++.